The Hidden Harvest: Unlocking Efficiency in East Java’s Farming Sector - Romadhona, Mochamad Kevin; Oktafenanda, Rachmat Dimas (Journal of Urban Sociology, 2025)
The agricultural sector is crucial for meeting global food and nutritional needs, with East Java Province in Indonesia having the highest yields and being the safest sector from the pandemic. To maximize land area, land efficiency is essential, using superior seed varieties, chemical fertilizers, efficient irrigation systems, and modern agricultural tools. This research focuses on the agricultural community in Trawas Mojokerto and the efficiency of agricultural land in Duyung Village. Most farmers use sickles, hoes, animals, simple machines, and tractors for agriculture. A survey of 100 farmers in Duyung Village revealed that 44 people use sickles as traditional tools, while 23 use livestock for ploughing. Tractors are used for efficiency and energy savings but are rarely used due to lack of counseling from government institutions. Technological tools are used for specific soil types and must be rented before use. The majority of farmers need counseling to learn about the latest tools, and government assistance is lacking. The study also found that 68.9% of farmers do not use printed rice seeds, while 31.1% use them. Long rice seeds are preferred due to their quality and resistance to pests. The majority of farmers use direct soil irrigation systems, which vary in soil fertility levels. Fertilizer use varies, with 77.8% using urea and 20% using compost and urea. The Duyung Village community is efficient in land management, with most farmers understanding the importance of efficiency.